2016
DOI: 10.1002/ejlt.201500267
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and polymorphic behavior of enzymatically produced sunflower oil based cocoa butter equivalents

Abstract: A multi-methodological approach was used to study the isothermal crystallization of cocoa butter (CB) in the presence of sunflower oil based cocoa butter equivalents (CBEs). pNMR, DSC, oscillatory rheology, XRD, and PLM were used for this purpose. All the techniques confirmed that at 20 degrees C isothermal crystallization of all the blends is a two-step process with formation of alpha crystals in the first step and formation of beta' crystals in the second step. The blends with high amount of CBEs contained m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…The total amount of DAGs in CB is typically 1.1–2.8% 65 . The different effects of DAGs on fat crystallization have been studied by many researchers, such as lowering the crystallization rate 66 , slowing down the kinetics of crystallization, both in terms of nucleation and crystal growth 67 , 68 , acting as crystal seeds and increasing the onset of crystallization 69 , or delaying the polymorphic transition of TAGs 27 . No significant difference ( P < 0.05) in the total amount of MAGs in the CB, CBE, and the blend was detected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total amount of DAGs in CB is typically 1.1–2.8% 65 . The different effects of DAGs on fat crystallization have been studied by many researchers, such as lowering the crystallization rate 66 , slowing down the kinetics of crystallization, both in terms of nucleation and crystal growth 67 , 68 , acting as crystal seeds and increasing the onset of crystallization 69 , or delaying the polymorphic transition of TAGs 27 . No significant difference ( P < 0.05) in the total amount of MAGs in the CB, CBE, and the blend was detected.…”
Section: Resultsmentioning
confidence: 99%
“…Kadivar et al . 27 synthesized a CBE using enzymatic acidolysis between high stearic high oleic sunflower oil (HSHO) or high oleic sunflower oil (HOSO), plus a mixture of palmitic and stearic acids. The SFC of 25% and 50% (w/w) blend of HOSO CBE and HSHO CBE mixed with CB had significantly lower SFC between 20–30 °C in comparison with CB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…). Kadivar et al () studied the changes in the growth and morphology of crystals in blends of CB and sunflower oil‐based CBE by PLM. These authors reported an inhibitory effect in the crystal growth process at increasing levels of SUU TAG in the blends.…”
Section: Resultsmentioning
confidence: 99%
“…[3,4] Cocoa butter contains high levels of saturated fatty acids, such as palmitic and stearic acids, as well as monounsaturated oleic acid. [6] Some of the common cocoa butter substitutes or alternatives are Lauric acid based formulations and hydrogenated vegetable oils, [7] but these fats are not usually accepted in food-based products due to their tendency to cause an increase in blood cholesterol levels. However, the continuous demand on cocoa butter for use in food and other products has caused its competitive pricing and scarcity on the market.…”
Section: Introductionmentioning
confidence: 99%